Technological study and chemical- archaeometric characterization of Roman opaque red glass from opus sectile decoration in the Lucius Verus Villa, 2nd century AD - Bandiera, Mario (2022)
Opaque red glass has been manufactured since the begging of glassmaking technology. However, it can be considered one of the most difficult colours to produce. It has been widely investigated by both glass science and archaeometry fields, providing vast literature. However, several aspects concerning its production during the Roman age are still unclear such as: where it was produced, which raw materials were used, and overall, how it was made. Moreover, the absence of written technical sources for Roman glass makes the investigation more complex. This research aims to investigate the production technology of opaque red glass during the 2nd century AD in the Roman Empire, in order to: 1. Identify which types of opaque copper red glass were manufactured in the Roman Empire during the 2nd century AD. 2. Investigate, through a multi-analytical approach, which factors determine the origin of the different red and orange hues (chemical composition, the nature of the colouring agent as well as their number and sizes). 3. To shed light on the technological aspects involved in making copper-red glass hues during the 2nd century AD. To reach these goals the research faced opaque red glass from three main different points of view. Although they are focused on distinct aspects, they will be interconnected. First, a literature review was necessary to identify the main features of copper red glass from a glass science point of view to understand the colouring agent, the formation and production of the colour. On the other hand, chemical analyses from previous archaeometric investigations were collected from the literature to make the history of opaque red glass from the Late Bronze Age until the medieval period. After this first step, the core of this work is the archaeometric investigation of the glass sectilia (sheets of glass) which decorated the villa of the Roman Emperor Lucius Verus. The glass sectilia are part of the Gorga collection, which is stored in the Soprintendenza Archeologica di Roma, and they represent an exceptional opportunity to study Roman glass technology of the 2nd century AD. These sectilia were chosen for this case study for two main reasons: they are well dated, attested to the 2nd century AD; they show the presence of several red and orange hues. This made it possible to examine the origin of the different red hues (chemical composition, colouring agent and specific production technology). The scientific investigation was conducted through a multi-analytical approach, which included: FORS, OM, EPMA, FEG-SEM, LA-ICP-MS, μXRD and μRaman spectroscopy. The production technology of opaque red glass (in this case only red brown type) has been studied through systematic laboratory reproductions. Iron and copper were tested to understand which raw materials could be employed, in which oxidation state iron should be added and the concentration needed to produce opaque red glass. Several procedures were attempted to recognise the most probable method used by the Roman glassmakers. This study outlined the history of the production of opaque copper-red glass, which could be very useful to understand the technological development of the glassmaking industry. The red glass sectilia investigated in this work revealed the presence of four red hues and three orange hues. Beyond enriching the literature of chemical analyses of opaque red glass dated to the 2nd century AD, these results have highlighted the use of more than one recipe used by the Roman glassmaker to broaden the chromatic scale of opaque red glass. Each red hue weas obtained through the accurate control of the raw materials, glass composition and heat treatments. The difficulties in making opaque red glass that emerged through the laboratory reproductions underlined that the good results could be achieved through accurate control of the melt redox condition through the correct glass composition and use of the appropriate raw materials. Likely, opaque red glass was not the result of fortune but of several failed experiments which allowed to master the colouring technique.